'A stairway that does its own climbing': the department store escalator and the promises of modernity, 1900–1950. Issue 1 (2nd January 2021) - Elvins, Sarah
ABSTRACT: This article explores the history of the department store escalator in the first half of the twentieth century in the United States. Department stores were crucial in adopting new technologies in the city. Many people first encountered 'moving staircases' in the aisles of the store. The installation of new escalators became an occasion for celebration, as stores emphasized their modernity and commitment to progress. Familiarity with riding on escalators could separate the urban sophisticate from the country bumpkin. Well into the 1940s, crowds greeted escalators with enthusiasm. For retailers, the technology offered new possibilities for store layouts and convenience for shoppers and employees. As the escalator became standard equipment in the modern store, the potential dangers posed to riders were downplayed.